Given:
1. Combining like terms (here terms 6x and 2x both contain x, then we can combine them):
![x^2+(6x+2x)+12=0,\\\\x^2+8x+12=0.](https://img.qammunity.org/2019/formulas/mathematics/high-school/8il0xo4ob8i4a3au3i1i6xr86qfqf96rye.png)
2. Distributive postulate:
![x^2+8x+12=(x+6)(x+2).](https://img.qammunity.org/2019/formulas/mathematics/high-school/dy8jc40tdmqtxkjr7k8u62c37bf0yc9jff.png)
The equation is
![(x+6)(x+2)=0.](https://img.qammunity.org/2019/formulas/mathematics/high-school/d2kwsmfv9k7e2gzjsg6kclkr1mbz9dov47.png)
3. Zero product postulate (zero product postulate state that if a product of two factors is equal to zero, then first factor is equal to zero or second factor is equal to zero):
![x+6=0 \text{ or } x+2=0.](https://img.qammunity.org/2019/formulas/mathematics/high-school/uzyj2vlr6gzuh66fb18tpba6my2fsypxsf.png)
4. Subtraction property of equality:
a) subtract 6 from the first equation:
![x+6=0\Rightarrow x+6-6=-6, \ x=-6.](https://img.qammunity.org/2019/formulas/mathematics/high-school/74plq01kiagk6fnu8sz0f878hg5x54cmbg.png)
b) subtract 2 from the second equation:
![x+2=0\Rightarrow x+2-2=-2, \ x=-2.](https://img.qammunity.org/2019/formulas/mathematics/high-school/63laqfpcci9you4a1tpe0i09rgrez8dgdb.png)